2021
DOI: 10.1186/s12913-021-07169-7
|View full text |Cite
|
Sign up to set email alerts
|

The underlying factors of excess mortality in 2020: a cross-country analysis of pre-pandemic healthcare conditions and strategies to cope with Covid-19

Abstract: Background Government responses to the pandemic varied in terms of timing, duration, and stringency, seeking to protect healthcare systems, whose pre-pandemic state varied significantly. Therefore, the severity of Covid-19 and, thus, excess mortality have been unequal across counties. This paper explores the geography of excess mortality and its underlying factors in 2020, highlighting the effects of health policies pre-pandemic and strategies devised by governments to cope with Covid-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Our results support the hypothesis that groups with sociodemographic vulnerabilities experienced the highest impact of excess mortality attributable to hospital saturation, with this impact having an unequal distribution within Mexico. In the European region, countries with high excess mortality, such as Bulgaria, Russia, and Serbia were impacted by diverse social barriers with difficulties to full adhere to social isolation policies (30,31). Two recent reports in England revealed that communities with high-density of care homes, with a high proportion of residents on income support, overcrowding conditions, and ethnic minorities were at higher risk of excess mortality and years of life lost due to the COVID-19 pandemic (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the hypothesis that groups with sociodemographic vulnerabilities experienced the highest impact of excess mortality attributable to hospital saturation, with this impact having an unequal distribution within Mexico. In the European region, countries with high excess mortality, such as Bulgaria, Russia, and Serbia were impacted by diverse social barriers with difficulties to full adhere to social isolation policies (30,31). Two recent reports in England revealed that communities with high-density of care homes, with a high proportion of residents on income support, overcrowding conditions, and ethnic minorities were at higher risk of excess mortality and years of life lost due to the COVID-19 pandemic (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reports in England revealed that communities with high-density of care homes, with a high proportion of residents on income support, overcrowding conditions, and ethnic minorities were at higher risk of excess mortality and years of life lost due to the COVID-19 pandemic (32,33). In Latin American countries, the impact of socioeconomic disparities was sharp mainly due to countries experiencing diverse social barriers to sustain lockdown mandates driven by low stipend support, a high proportion of their population working in informal conditions, and uncovered health care basic needs even within healthcare workers personnel (3,30,34). Nevertheless, this evidence and the comparison between countries should be interpreted with caution given the variation in COVID-19 dynamics, within-country gradients of sociodemographic inequalities, and the profiles of high-risk comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the general correlation still persists. Kapitsinis (2021) analyzed state responses in 79 countries worldwide. In his analysis of to the pandemic, he looked at the mortality rates within the state. Privatization of health care, underfunding of health care and delayed implementation of strategies to contain and mitigate the coronary pandemic were the main causes of excess mortality.…”
Section: Theories and Hypothesismentioning
confidence: 99%
“…Because change will not happen instantaneously, we empirically estimate NPI effectiveness by including various lags in our model: t + 1 (2), t + 2 (4), and t + 3 (6 weeks) after their introduction. While Covid‐19 deaths or excess mortality are important aspects of the debate (e.g., Kapitsinis, 2021 ; Mendez‐Brito et al, 2021 ), we opted not to use those figures. The main concern is that there is no theoretical reason why deaths should be more directly affected by NPIs than cases.…”
Section: Research Design and Variablesmentioning
confidence: 99%